Perceptions of Islamic Studies, Sharia, and Law Students Towards the Use of Artificial Intelligence in English Learning - Safa Alrumayh; Nahid Ayad; Khuloud Alouzi; DafaAllah Ibrahim; Mahmoud Abdullah; Mohieddin Masoud; Majdy Kasheem (Action Research Journal Indonesia (ARJI), 2025)
The rapid advancement of Artificial Intelligence (AI) technologies is significantly transforming our understanding of educational landscapes worldwide, prompting new pedagogical models and reshaping how students interact with language learning tools. Within traditionally text-centric disciplines such as Islamic Studies, Sharia, and Law, the integration of AI into English language education presents both opportunities and challenges that warrant critical inquiry. This study investigates the perceptions, usage patterns, and pedagogical implications of AI tools in English learning among 250 students in these fields. Drawing from sociocultural learning theory and Islamic pedagogical ethics, a mixed-methods approach was employed, with quantitative data gathered through a 20-item Likert-scale questionnaire. Findings reveal positive attitudes toward AI, especially in writing improvement, vocabulary acquisition, and Arabic-English translation. Students also acknowledged AI’s utility in linking complex legal and religious concepts to English equivalents. However, responses varied on AI’s accuracy in translating fiqh and legal terminology, with concerns about interpretive limitations and doctrinal precision. Interestingly, while experts warn of AI’s contextual shortcomings, students reported low concern, suggesting a gap in AI literacy. The study highlights the need for critical pedagogical strategies that foster AI competency while maintaining ethical and theological sensitivity.